Living in My Voice and Choice: A Poetry-Based Mindfulness in EFL Classroom - Piscayanti, Kadek Sonia (Universitas PGRI Semarang, 2022)
Poetry is an expression of thoughts and feelings with words. Poetry in language learning is the bridge to communicate ideas and unheard voice. This research is aimed at exploring the voice and choice, the emotion and expression of language learners from three poetry of three different poets in EFL classroom with mindfulness approach. Mindfulness approach allows them to be more aware of the novel situation, flexible to context, having multi perspectives, and create a production. The method used is narrative inquiry with mindful journal as instrument. The findings showed that the poetry the learners write have the power to explore the learners’ ability in stimulating their truest voice and choice from within, as well as to stimulate their language creativity and productivity. By having sensitivity, the creativity is born and productivity is born too. In the context of language learning, the language learners are more open about their identity, their purest voice, and their alternative solution of life’s problem. Mindfulness is not only as tool to stimulate the voice but also stimulate the choice of the poets.